The peculiarities of stylistic syntax of the narrative "In the depth of rains" by Mykola Vinhranovskyi - Калашник, Юлія Іванічна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The article concentrates on the syntactic organization of the narrative’s monologues in the narrative "In the depth of rains" by Mykola Vinhranovskyi. It is determined by the variety of expressive means, irony, cinematographic representation. The research work analyses different methods and schemas of stylistic syntax, which are prominent in the writer’s creative manner, – repetitions, gradation, amplification, etc. The article regards representative syntactic means of the key image of the rain.